Getting Started with Kubernetes : Extend your containerization strategy by orchestrating and managing large-scale container deployments, 3rd Edition /: Extend your containerization strategy by orchestrating and managing large-scale container deployments, 3rd Edition. (2018) - Baier, Jonathan; White, Jesse
No abstract available